THE EFFECT OF PROBLEM BASED LEARNING MODELS AND LEARNING MOTIVATION ON LEARNING OUTCOMES AND PROBLEM SOLVING ABILITY IN ANIMAL LIFE CYCLE MATERIAL AT SD NEGERI 174581 SIPAHUTAR - Hanna Silitonga; Hasruddin Hasruddin; Daulat Saragi (Sensei International Journal of Education and Linguistic, 2023)
Objective this research is to find out influence in a manner simultaneously , the influence of learning models based problem and motivation Study to results learning and ability solving problem students at SDN 174581 Sipahutar . This research is study experiment pseudo . Research data collected with test ability solving students and tests results learn science students . As for the amount sample in this research is 45 students with 26 students man boys and 19 students girl . Testing hypothesis done with use analysis manova . Research results show that , (1) exists influence application of the learning model based problem to results Study student . (2) There is the influence of learning models based problem to ability solving problem students at SDN 174581 Sipahutar . (3) There is the influence of motivational models Study to results Study students on the material cycle life animal . (4) There is influence motivation Study to ability solving problem student .